Case report: Endoscopic endonasal transposterior clinoid approach for resection of posterior clinoid process meningioma: technical notes and literature review - Awyono, Steven; Takeuchi, Kazuhito; Ito, Eiji; Nagata, Yuichi; Golden, Nyoman; Mahadewa, Tjokorda Gde Bagus; Saito, Ryuta (Frontiers in Oncology, 2024)
Posterior clinoid process (PCP) meningioma is an exceedingly rare entity. It remains the most challenging skull base lesion for neurosurgeons due to its treacherous location that insinuates amongst critical neurovascular structures. This article will describe the technical notes using the endoscopic endonasal approach that provide the earliest devascularization and detachment of the tumor PCP meningioma.We are introducing the surgical implementation of an endoscopic endonasal approach to removing PCP meningioma. Furthermore, we perform a literature review of posterior clinoid process meningioma that undergoes surgical intervention, then summarize the benefits and limitations of each approach.We present a case of right PCP meningioma that was removed using an endoscopic endonasal approach through the transposterior clinoid corridor in a 52-year-old-woman. We describe the technical notes in performing this approach to have the earliest devascularization and detachment of the tumor by performing posterior clinoidectomy. Safe tumor removal is performed with a wide and clear view of the surrounding neurovascular structure. Based on our database search, we found nine articles reported on the surgical management of PCP meningiomas, with a total number of 15 cases. All of the reported cases performed the tumor removal using the transcranial approach.The endoscopic endonasal transposterior clinoid approach circumvents all disadvantages faced by the traditional transcranial approach, providing the earliest approach to devascularized and detaching the tumor from its attachment at PCP. This approach demonstrates safety and efficacy, making it an acceptable alternative for PCP meningioma resections.